Dynamic changes in the glycocalyx and clinical outcomes in patients undergoing endovascular treatments for large vessel occlusion - Liang, Dan; Zeng, Xiuli; Yao, Mingzheng; Li, Fei; Lin, Jiaxing; Zhang, Liang; Liu, Jialin; Huang, Li'an (Frontiers in Neurology, 2023)
Purpose: We aimed to verify the prognostic value of the glycocalyx as a marker of blood‒brain barrier damage in acute ischemic stroke patients undergoing endovascular therapy. Methods: We recruited patients with large vessel occlusion who were undergoing recanalization, and we tested the glycocalyx at multiple time points. On the basis of the 90-day follow-up data, the patients were divided into a survivor group and a nonsurvivor group. In addition, neurological function was tracked, and patients were divided into a neurological deterioration group and a group without neurological deterioration. Associations between outcomes and dynamic changes in the glycocalyx were determined using a linear mixed model, and significant factors were used as covariates. Results: Nonsurvivors and patients with neurological deterioration had significantly higher syndecan-1 concentrations than survivors and patients without neurological deterioration, and syndecan-1 tended to decline after endovascular therapy (p<0.05). The increased level of syndecan-1 at 36h after endovascular treatment was positively correlated with the National Institute of Health Stroke Scale score for neurological deterioration (r=0.702, p=0.005). However, there was no significant difference in the level of hyaluronic acid or heparan sulfate in plasma between patients with different clinical outcomes. Conclusions: Pre-reperfusion syndecan-1 levels in patients with large vessel occlusion stroke are associated with 90-day mortality, and the re-degradation of syndecan-1 is positively associated with neurological deterioration.